2021
DOI: 10.1001/jamasurg.2021.1557
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Meaning of Recovery to Patients Undergoing Abdominal Surgery

Abstract: IMPORTANCE Postoperative recovery is difficult to define or measure. Research addressing interventions aimed to improve recovery after abdominal surgery often focuses on measures such as duration of hospital stay and complication rates. Although these clinical parameters are relevant, understanding patients' perspectives regarding postoperative recovery is fundamental to guiding patient-centered care.OBJECTIVE To elucidate the meaning of recovery from the perspective of patients undergoing abdominal surgery. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
0
31
0
2
Order By: Relevance
“…18,19 Recent research has shown that recovery is both multi-phased and multi-dimensional, and can vary between individuals. 3,19 Furthermore, with an ageing population, there are more elderly patients with multiple comorbidities. Understanding what 'good' quality of life means to them will help clinicians to provide tailored treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 Recent research has shown that recovery is both multi-phased and multi-dimensional, and can vary between individuals. 3,19 Furthermore, with an ageing population, there are more elderly patients with multiple comorbidities. Understanding what 'good' quality of life means to them will help clinicians to provide tailored treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this may lack HRQoL information. Patient‐centeredness is an important criteria for judging healthcare quality, and PROMs provide a mechanism for better understanding the specific needs of individual patients 18,19 . Recent research has shown that recovery is both multi‐phased and multi‐dimensional, and can vary between individuals 3,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Patients' perceptions of recovery do not merely pertain to single symptoms, but include returning to habits, social relations, regaining independence, and psychological and mental strains. 4,121 That is why exploring how the four dimensions of recovery were represented is important. The results indicate that 13/25 instruments had items in all four dimensions and 9/ 25 had items in three dimensions, showing that the concept of recovery is quite well assessed in the instruments identified here.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is becoming increasingly di cult to identify whether treatments exert signi cant effects on postoperative outcomes using these traditional variables (Yoon et al, 2020). Furthermore, these variables have been reported to deviate greatly from patient-perceived postoperative recovery (Rajabiyazdi et al, 2021). In contrast, the Quality of Recovery-15 (QoR-15) questionnaire can provide a meaningful and overall assessment of patient-centered postoperative recovery (P. S. Myles 2018) and has been recommended as an endpoint in clinical studies investigating postoperative recovery (Kleif, Waage, Christensen, & Gögenur 2018; P. S. Myles et al, 2018).…”
Section: Introductionmentioning
confidence: 99%